Schools and Private Teaching Institution in Turkish Educational System An Analysis in a Multiparadigm Perspective - Turan, Selahattin; Armagan, Yasir; Cakmak, Esra (ISTANBUL UNIV, FAC LETTERS, DEPT SOCIOLOGY, 2015)
Paradigms which present us a world view for examining a concept or subject are categorized as radical humanist paradigm, radical structuralist paradigm, interpretive paradigm and functionalist paradigm. With their assumptions paradigms that provide us oppurtunity to examining the subjects thoroughly want to dominate a definite subject or/and field. As a result of this situation paradigm war appears. In this war process associated to politics, not the best paradigm but the paradigm which has more supporters tends to win this war and this is the most crucial problem. Besides it is hard to say that only one paradigm dominates the field in modern sociology. Considering that it isn't likely to explain a concept with assumptions of adopted paradigm, it can be said that it will be more correct to analyze a concept in a multiparadigm perspective. In this context, the aim of this research is to analyze educational system and schools in multiparadigm perspective.
Keywords: Paradigm; school; educational system; Sociology